Knowledge products emanating from community-based breeding programs are integrated into animal science programs in institutions of higher learning - Belay, Berhanu; Haile, Aynalem; Mourad, Rekik; Getachew, Tesfaye; Rischkowsky, Barbara (International Livestock Research Institute, 2024)
The community-based breeding program (CBBP) has shown remarkable success. It pools the village's small ruminant flock, measures and records performance and pedigree data, and conducts genetic evaluation. The program has led to tangible achievements, such as improved productivity, increased farmers' income, and enhanced family food security. For example, farm-level meat consumption increased from the slaughter of one sheep per year to three. These outcomes inspire hope for the future of sustainable animal productivity. Despite being launched in 2009 with the collaboration and support of research institutes, livestock extension services, the International Livestock Research Institute (ILRI), the International Centre for Agricultural Research in the Dry Areas (ICARDA), and BOKU, the participation of Ethiopian universities in the CBBP was notably lacking, considering their extensive reach across all regions and diverse Agro-ecological settings. The scaling approach initiated based on the framework developed by Mueller et al. (2019) has triggered the engagement of more partners, including universities, in the expansion of sheep and goat CBBPs. Ethiopian Universities are latecomers; however, they are supported by more than 62 CBBP villages, benefitting 6300 households and investing 1.2 million USD in enhancing teaching, research and community engagement. The practice and knowledge of CBBP are also integrated into the curriculum by influencing the curriculum policy. More than 31 curricula that benefited more than 1120 students per year have integrated CBBP into the UG programs. The lessons from the undergraduate (UG) programs have also given the impetus to integrate CBBP into the postgraduate (PG) program, and more than 43 curricula have integrated CBBP into the curricula, which benefits 345 students per year. The survey conducted to ascertain the relevance of supporting and establishing CBBP under the support of universities and the integration of the CBBP knowledge in the curriculum is highly (88-100%) endorsed in the face of the university community.